Reviewing the Explanations of the Unity of All Being Principle According to Ayatollah Javadi Amolie - Ehsan Fattahi Ardakani (حکمت اسرا, 2015)
It is the claim of mysticism that the being is one and that one is the necessary Being. It has been tried to present arguments for this claim (existential unity of God). The question of the present study is that according to Ayatollah Javadi Amoli what deficiencies could be found in these arguments and is there any way to demonstrate this claim or not. In this paper we shall investigate the arguments for the unity of all being, then we will explain their deficiencies according to Ayatollah Javadi Amoli, and finally his solution for this problem will be presented. He believes that the solution is the very Proof of the Veracious addressed by Allameh Tabataba'i that by adding a comment to it about the infinity of the necessary being the claim for unity of all being will be proved.